Historical Review of Robbery - Supatashvili, Ketevan (European Scientific Journal, ESJ, 2017)
The subject of the research topic is of a serious criminal offense such as robbery. The present paper investigates robbery as one of the most dangerous forms of seizure of other’s property accompanied by using violence or threat of violence which endangers life or health. The research studies whether robbery is properly attributed to property crimes when robbery is directly related to life or health-threatening violence. The major subject of the research is to make fundamental criminal analysis of robbery as one of the most severe and frequently committed crime; also, to identify its place in the Criminal Code on the basis of comparing it with premeditated murder motivated by self-interest. The research gives historical review of robbery considering the European practice and aims to contribute to improvement of the legislation of Georgia.